2020
DOI: 10.1111/jce.14769
|View full text |Cite
|
Sign up to set email alerts
|

A novel screening tool to unmask potential interference between S‐ICD and left ventricular assist device

Abstract: Introduction: In patients with a left ventricular assist device (LVAD), the subcutaneous implantable cardioverter-defibrillator (S-ICD) can be an alternative to transvenous ICD systems due to reduced risk of systemic infection, which could lead to extraction of the ICD as well as the LVAD. S-ICD eligibility is lower in patients with LVAD than in patients with end-stage heart failure without LVAD. Several reports have shown inappropriate S-ICD therapy in the coexistence of LVAD and S-ICD. The aim of the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…In order to unravel potential device-device interference between S-ICD and LVAD, we also performed the device-based screening test. The device-based screening test uses a functional S-ICD generator connected to an S-ICD lead and fixed in the appropriate position with adhesive tape and contact gel as previously described [ 10 ]. This screening test aims to better imitate an implanted S-ICD system in situ and allows to test for correct sensing and potential electromagnetic interference.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to unravel potential device-device interference between S-ICD and LVAD, we also performed the device-based screening test. The device-based screening test uses a functional S-ICD generator connected to an S-ICD lead and fixed in the appropriate position with adhesive tape and contact gel as previously described [ 10 ]. This screening test aims to better imitate an implanted S-ICD system in situ and allows to test for correct sensing and potential electromagnetic interference.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that S-ICD eligibility in patients with LVAD is lower compared to patients with heart failure in general [ 5 , 10 ]. A novel device-based S-ICD screening tool was found to unravel potential device-device interference between LVAD and S-ICD [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cases of the automated screening test unable to deliver a result have been previously reported and are often due to paced QRS complex, low R wave amplitudes, and electromagnetic interferences. 8,9 The ECG-based screening test was performed as standard of care, but was not the main focus of our study, since this has already been largely examined in ACHD patients in previous studies. 2,3,5,7,10 Furthermore, Wang et al propose a comparison of S-ICD eligibility in different positions (standing and supine) on the left and right parasternal position using McNemar's chi-square test.…”
mentioning
confidence: 99%